New in vitro effects of clopidogrel on platelets in hyperlipidemic and healthy subjects - ŞENER, AZİZE; ÖZSAVCI, DERYA; OBA, RABİA (GALENOS YAYINCILIK, 2010)
Objective: We aimed to detect novel in vitro effects of clopidogrel on platelets by assessment of the following parameters: malondialdehyde, glutathione, nitrite, aggregation response, and expressions of P-selectin, fibrinogen, apolipoprotein A1, apolipoprotein B, and phosphatidylserine. Materials and Methods: Platelets were obtained from healthy (n: 9) and hyperlipidemic (n: 9) volunteers. Expressions of P-selectin, fibrinogen, apolipoproteins A1/B and phosphatidylserine with and without clopidogrel were assayed by flow cytometry. Malondialdehyde, glutathione, aggregation and nitrite levels were also assayed. Results: Without clopidogrel, the baseline values of platelet aggregation, malondialdehyde, and expressions of P-selectin, fibrinogen and phosphatidylserine were significantly higher, whereas nitrite and expression of apolipoproteins A1/B were significantly lower in hyperlipidemics than in the healthy group. In both groups, clopidogrel significantly reduced aggregation and expression of fibrinogen, but it elevated nitrite levels. Clopidogrel significantly decreased P-selectin and phosphatidylserine expression and malondialdehyde but increased expressions of apolipoproteins A1/B only in hyperlipidemics. Conclusion: It seems that clopidogrel has some new in vitro antiplatelet effects. The present study is a basic in vitro study to suggest new insights into the effects of clopidogrel on platelet functions. (Turk J Hematol 2010; 27: 99-108)
Keywords: Platelets; hyperlipidemia; clopidogrel; apolipoprotein A1; apolipoprotein B; oxidative stress; nitrites; phosphatidylserine; P-selectin; glycoproteins IIb/IIIa; LOW-DENSITY-LIPOPROTEIN; GLYCOPROTEIN IIB/IIIA; P-SELECTIN; NORMOLIPEMIC VOLUNTEERS; SECONDARY PREVENTION; ACTIVATED PLATELETS; BINDING; INHIBITION; EXPRESSION; APOPTOSIS